Military necessity : the art, morality and law of war / Nobuo Hayashi. - Hayashi, Nobuo (Cambridge University Press, 2020)
What does it mean to say that international humanitarian law (IHL) strikes a realistic and meaningful balance between military necessity and humanity, and that the law therefore 'accounts for' military necessity? To what consequences does the law 'accounting for' military necessity give rise? Through real-life examples and careful analysis, this book challenges received wisdom on the subject by devising a new theory that not only reaffirms Kriegsräson's fallacy but also explains why IHL has no reason to restrict or prohibit militarily unnecessary conduct on that ground alone. Additionally, the theory hypothesises greater normative significance for humanitarian and chivalrous imperatives when they conflict with IHL rules. By combining international law, jurisprudence, military history, strategic studies, and moral philosophy, this book reveals how rational fighting relates to ethical fighting, how IHL incorporates contrasting values that shape its rules, and how law and theory adapt themselves to war's evolutions.